Linac failure diagnostics - Akchurin, Yu.I.; Boriskin, V.N.; Ivahnenko, M.V.; Levandovsky, S.P.; Orlova, E.I.; Savchenko, A.N. (Вопросы атомной науки и техники, 1999)
The data processing subroutine from 60 discrete detectors is developed for the operating control system [1] of the technological linac. It uses a dialogue regime of work. This subroutine allows us to find a basic cause of linac failures in certain circuit, as well as the site of fault. Recommendations for repair are also given.